Avaliação dos efeitos da associação entre a crotamina de Crotalus durissus terrificus e fármacos clássicos no tratamento da leishmaniose cutânea experimental - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
Leishmaniasis is a serious public health problem affecting areas of temperate and tropical climate. Currently, there are 1.3 million cases and approximately 20 thousand deaths per year, partly due to the treatments that present several inadequacies, serious side effects and therapeutic failure of up to 65% suggesting urgency in the discovery of alternative therapies to combat this disease. The objective of this study was to evaluate the efficacy and toxicological effects of the association between crotalin (CTA) of Crotalus durissus terrificus and classical drugs used in the therapy of leishmaniasis. Preliminary study identified the best combination between CTA and Glucantime® (GLU) or Pentamidine (PEN) against the promastigotes of L. amazonensis. In the present study, the GLU formulations were characterized as G1 (GLU 300 μg / mL + CTA 100 μg / mL) and G2 (GLU 300 μg / mL + CTA 3.125 μg / mL) and PEN 0.05 μg / mL + CTA 100 μg / mL) and P2 (PEN 0.05 μg / mL + CTA 3.125 μg / mL). In vitro, the treatments were evaluated on inhibition of growth of promastigotes, amastigotes, production of nitric oxide, cytokines and cytotoxicity of treatments on lineage cells. Molecular affinity and molecular characterization of CTA and GLU or PEN were also analyzed. In vivo, the experimental groups were named G5 (GLU 300 mg.kg-1 + CTA 5 mg.kg-1) and G6 (PEN 4 mg.kg-1 + CTA 5 mg.kg-1) and treatments were performed for eight alternate days. After 48h of the end of treatment the animals were killed, and the paws were removed in the first joint above the lesion for weighing. Blood, paw, lymph node, kidneys, liver and spleen were then removed for further experiments. The blood from each animal was centrifuged and the serum separated for biochemical and immunological analysis. Combinations G1, G2, P1 and P2 have been shown to be more effective against promastigotes, or equally efficient against amastigotes and less cytotoxic than drugs alone. Formulations G1, G2, P1 and P2 did not alter the cellular responses of NO, however, G1 and G2 stimulated TNF-α, while P1 and P2 stimulated IL-12. Docking, DM and SPR demonstrated molecular affinity between CTA to GLU and PEN with a concentration-dependent profile. In vivo, experimental treatments (G5 and G6 groups) were shown to be more effective than the drugs alone (G3 and G4 groups) in reducing the parasitic load of the paw and lymph node, however, there was no decrease in lesion size. The animals did not lose body mass and, together with the biochemical analysis data, showed low toxicity and adequate treatment tolerability. Groups G5 and G6 primarily exhibited a Th1 profile with a marked increase in the production of IFN-γ, TNF-α and IL-17α while, on the other hand, they inhibited IL-10. The combination of CTA increased the efficacy of treatment and decreased in vitro cytotoxicity of GLU and PEN against L. amazonensis, modulated the cellular immune response. A of CTA with both drugs was shown to be more effective than the drugs alone in reducing the parasite burden without showing systemic toxicity. This pharmacological combination approach has been shown to be promising for the experimental treatment of cutaneous leishmaniasis. As future prospects, it will be necessary to explain the mechanisms involved in inhibiting the parasite and reducing the cytotoxicity provided by the experimental treatments.
Keywords: Leishmaniose Cutânea; Crotamina; Fármacos antileishmania; Terapia experimental; CIÊNCIAS BIOLÓGICAS